Methylation of the Glucocorticoid Receptor (NR3C1) in Placenta Is Associated with Infant Cry Acoustics - Sheinkopf, Stephen J.; Righi, Giulia; Marsit, Carmen J.; Lester, Barry M. (Frontiers in Behavioral Neuroscience, 2016)
Epigenetic mechanisms regulating expression of the glucocorticoid receptor gene (NR3C1) promoter may influence behavioral and biological aspects of stress response in human infants. Acoustic features of infant crying are an indicator of neurobehavioral and neurological status not yet investigated in relation to epigenetic mechanisms. We examined NR3C1 methylation in placental tissue from a series of 120 healthy newborn infants in relation to a detailed set of acoustic features extracted from newborn infant cries. We identified significant associations of NR3C1 methylation with energy variation in infants’ cries as well as with the presence of very high fundamental frequency in cry utterances. The presence of high fundamental frequency in cry (above 1 kHz) has been linked to poor vocal tract control, poor regulation of stress response, and may be an indicator of poor neurobehavioral integrity. Thus, these results add to evidence linking epigenetic alteration of the NR3C1 gene in the placenta to neurodevelopmental features in infants.